Pengembangan Lembar Kerja Peserta Didik Berbasis Pendekatan Science, Technology, Engineering, And Mathematics (STEM) Dalam Mata Pelajaran Ilmu Pengetahuan Alam Di Kelas VI - Neti suryani Suryani; Endang Widi Winarni; Irwan Koto (UNIB Press, 2022)
This study aims to describe the development, feasibility, and response of students to STEM-Based LKPD with Theme 8 Bumiku for Class VI in Science Subjects. The type of research is research and development by modifying the Sugiyono model adopting 6 steps, namely potential problems, planning information gathering, product design, design validation, product revision, product testing. Research data obtained through questionnaires, interview guidelines, validation sheets, and student responses. Aspects that are validated include the feasibility of the material, language, presentation and graphics. The results of the research and development show that: 1) STEM-based LKPD was developed through six stages of development, namely the potential problem stage, information gathering, planning, product design, design validation, product revision, limited trial; STEM-based worksheets meet the feasibility in the aspects of material, language, presentation, and graphics that are suitable for use in learning because on average each feasibility obtains valid results and the reliability is very strong; 3) The response of the STEM-based LKPD is very good because the relationship between science and mathematics content has been integrated quite well. Based on the results of research and development, it is concluded that STEM-based worksheets are very suitable for use in learning science content for grade VI elementary school students.